2016
DOI: 10.1111/1753-6405.12498
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk of violence against people with and without disabilities: findings from an Australian population‐based study

Abstract: Objectives: There are no population-based estimates of the prevalence of interpersonal violence among people with disabilities in Australia. The project aimed to: 1) estimate the prevalence of violence for men and women according to disability status; 2) compare the risk of violence among women and men with disabilities to their same-sex non-disabled counterparts and; 3) compare the risk of violence between women and men with disabilities. Methods:We analysed the 2012 Australian Bureau of Statistics Survey on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 25 publications
6
53
1
11
Order By: Relevance
“…The few existing studies on GBV among PWDs indicate that PWDs are at equal or greater risk of GBV compared to their peers without disabilities [5][6][7][8][9][10][11][12][13][14]. PWDs report multiple forms of violence during their lifetime, by multiple perpetrators and for longer periods, compared to people without disabilities [5].…”
Section: Gbv Among People With Disabilitiesmentioning
confidence: 99%
“…The few existing studies on GBV among PWDs indicate that PWDs are at equal or greater risk of GBV compared to their peers without disabilities [5][6][7][8][9][10][11][12][13][14]. PWDs report multiple forms of violence during their lifetime, by multiple perpetrators and for longer periods, compared to people without disabilities [5].…”
Section: Gbv Among People With Disabilitiesmentioning
confidence: 99%
“…The multiple disabilities of women with severe mental illness appear to render them especially vulnerable to such exploitation. Disabled persons are known to experience significantly more violence (physical, sexual and intimate partner violence and stalking/ harassment) than those without disability, as shown in a recent Australian study of more than 17,000 adults (Krnjacki et al, 2016). This study noted gender differences: women with disabilities were more likely to experience sexual and partner violence whereas men with disabilities were more likely to experience physical violence.…”
Section: Introductionmentioning
confidence: 56%
“…Accordingly, access to services and support varied with individual circumstances, giving rise to inequity within the system. Studies also revealed persistent poor quality of life for Australians with disabilities, citing high levels of social exclusion and risk of violence, and low levels of income and Labor market participation (OECD 2009;Milner et al 2014;Mithen et al 2015;Kmjacki et al 2016).…”
Section: Background Of the Reformsmentioning
confidence: 99%